Worldwide distribution, risk factors, and temporal trends of testicular cancer incidence and mortality: A global analysis - Huang, Junjie; Chan, Sze Chai; Tin, Man Sing; Liu, Xianjing; Lok, Veeleah Ting-Ting; Ngai, Chun Ho; Zhang, Lin; Lucero-Prisno, Don Eliseo; Xu, Wanghong; Zheng, Zhi-Jie; Chiu, Peter Ka-Fung; Ng, Anthony Chi-Fai; et al. (NLM (Medline), 2022)
BACKGROUND: Testicular cancer is a common malignancy among young males in western countries. OBJECTIVE: To examine the global disease burden and trends of testicular cancer incidence and mortality by age and country, and their associations with human development index (HDI), gross domestic product (GDP), lifestyle habits, and metabolic risk factors. DESIGN, SETTING, AND PARTICIPANTS: We retrieved the Global Cancer Observatory database for the testicular cancer incidence and mortality in 2020; the World Bank for GDP per capita; the United Nations for HDI; the WHO Global Health Observatory for prevalence of smoking and alcohol drinking; and the Cancer Incidence in Five Continents, WHO mortality database, Surveillance, Epidemiology, and End Results programme and Nordic Cancer Registries (NORDCAN) for trend analysis. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: We presented the testicular cancer incidence and mortality using age-standardised rates. We examined their associations with HDI, GDP, smoking, alcohol drinking, physical inactivity, overweight, obesity, and medical conditions including diabetes, hypertension, and hypercholesterolaemia by linear regression. We estimated the 10-yr trend of incidence and mortality by joinpoint regression with average annual percentage change with 95% confidence intervals in different age groups. RESULTS AND LIMITATIONS: There was a wide variation in the testicular cancer burden with the highest mortality found in low-income countries, and the regions of Central America and South America, while the highest incidence was observed in high-income countries, especially in Western and Northern Europe. We found a positive association for HDI, GDP, alcohol drinking, inactivity, overweight, obesity, and hypercholesterolaemia with testicular cancer incidence, while a negative correlation was observed between GDP and mortality of testicular cancer. Globally, there was an overall increasing incidence trend of testicular cancer for the past decade, particularly in younger males; the mortality trends of testicular cancer were relatively stable. However, we did not analyse the trend of different stages and subtypes of testicular cancer due to data unavailability. CONCLUSIONS: There was a global variation in the testicular cancer burden associated with HDI, GDP, alcohol drinking, inactivity, overweight, obesity, and hypercholesterolaemia. Testicular cancer had an increasing incidence but decreasing mortality. The increasing testicular cancer incidence in the younger population is of concern and calls for early detection and preventive interventions. PATIENT SUMMARY: Globally, testicular cancer incidence had been increasing particularly in the younger population, although its deaths rates had been decreasing. Socioeconomic indices, alcohol drinking, inactivity, overweight, obesity, and high plasma lipid levels are associated with testicular cancer incidence and mortality.
Keywords: Alcohol Drinking; Incidence; Mortality; Smoking; Temporal Trend; Testicular Cancer